(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
A series of symmetrical diaryliodonium salts were prepared successfully in high yields following the Olofsson procedure. These salts were stirred with aqueous solution of NaBF4 to exchange the OTf- anion to BF4-. Different conditions were investigated to fluorinate these salts, including fluorinating reagents, solvents, reaction time, and solvents. Only p-fluoroarenes without any isomers were obtained in high yields during the fluorination of these salts.